Papers of Dame Ivy Wedgwood - Wedgwood, Ivy, Dame, 1896-1975. (1928)
Correspondence, diaries, subject files, speeches, minutes, reports, photographs and publications relating to Dame Ivy Wedgwood's political career. There is also correspondence and printed material relating to Lady Knox and her participation in the Australian Women's National League.
Manuscript reference no. : MS 5159.
Guide to collections of manuscripts relating to Australia
Also available online
Senator for Vic. 1950-1971 (retired), first woman elected to the Senate for Victoria. She was a campaigner for improved facilities for handicapped people, was the first woman to chair a Senate committee and a was a member of the group that met in 1944 to found the Liberal Party.
Keywords: Wedgwood, Ivy, -- Dame, -- 1896-1975 -- Archives; Politicians -- Australia -- Archives; Politicians; Federal politicians